Bridges - Miller, David (Book Sales, Incorporated, 2006)
This is the latest title in Compendium's new "Panoramic View Series" - huge coffee-table sized books, which use 16-inch wide pages to present the most beautiful panoramic views of the world's heritage and countryside. It features 212 full colour photographs, mainly single- and double-page spreads.